THE CORRELATION BETWEEN KNOWLEDGE AND FAMILY SUPPORT ABOUT SECONDARY PHYSICAL CHANGES IN PUBERTY WITH SELF-CONCEPT IN ADOLESCENT WOMEN AGED 13-15 YEARS AT MTSN 9 JOMBANG - Nurul Agustin; Ambar Asnaningsih (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
The physical development of adolescents that is so prominent and not the same for everyonecauses anxiety about their physical development it will also affect their self-concept. Lack ofknowledge and family support will make adolescent self-concept more negative. The purposeof this study was to determine the relationship between knowledge and family supportregarding secondary physical changes during puberty and self-concept in young women aged13-15. The research design used is correlational research. The population studied was youngwomen aged 13-15 years at MTSN 9 Jombang in 2022 using a purposive sampling techniqueto obtain a sample of 56 female students. The research instrument used was a questionnairesheet. The results of the study were then analyzed using the contingency coefficient. Theresults of the knowledge research showed that most of them had less knowledge, namely 31respondents (55.4%). The results of the research on family support show that most of themprovide less support, namely as many as 32 respondents (57.1%). The results of self-conceptresearch showed that most of the respondents' self-concept was negative, namely as many as37 respondents (66.1%). The results of statistical tests using the contingency coefficient testshow a significance level of 0.000 and 0.000 <α (0.05), meaning that there is a relationshipbetween knowledge and family support about secondary physical changes during pubertywith self-concept in young women aged 13-15 years at MTSN 9 Jombang in 2022.